1973
DOI: 10.1017/s0021859600059013
|View full text |Cite
|
Sign up to set email alerts
|

In vivomeasurements of the production rates of bacteria in the rumen

Abstract: SummaryThe production rates of bacteria have been measured in the rumen of zebu calves and buffalo calves. The animals were fed green oat continuously at 2 h intervals. [35S]sodium sulphate was fed to the animals for 5 days at 2 h intervals by mixing in the feed. On the sixth day the radioactive feed was stopped and replaced by non-radioactive feed. The decline in the specific radioactivity of bacterial cells in the rumen as a function of time was taken for calculatingt/2. Simultaneously rumen volume was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…There are few reports on the disappearance rates of bacterial protein in the rumen. Singh et al (1973) labelled rumen bacteria with 35S0,-enriched feed and reported disappearance rates of activity of 2.30 and 2.68 /d from the rumen of buffalo and zebu cattle respectively. However, this technique does not measure a loss of activity from a constituent of bacterial protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports on the disappearance rates of bacterial protein in the rumen. Singh et al (1973) labelled rumen bacteria with 35S0,-enriched feed and reported disappearance rates of activity of 2.30 and 2.68 /d from the rumen of buffalo and zebu cattle respectively. However, this technique does not measure a loss of activity from a constituent of bacterial protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique does not measure a loss of activity from a constituent of bacterial protein. In a second study, Singh et al (1974) added ~~-[U-'~C]leucine-labelled cultured bacteria into the rumen of buffalo calves and estimated disappearance rates of 4.46 and 4.87/d. These bacteria may, however, have failed to equilibrate between the liquid and solid phases before being washed from the rumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there would be significantly less analytical load than with alternative methods (e.g. Singh et al 1973;Walker & Nader, 1975). The applicability of the proposed method for animals at pasture or given feed infrequently should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent calculation of the amount of microbial protein that passes from the rumen or abomasum is dependent on estimation of flow rate of digesta from the rumen or into the duodenum; this usually requires total collection of digesta from re-entrant cannulae (MacRae, 1975), or collections from simple cannulae fitted to animals infused with digesta markers and given feed at frequent intervals (Faichney, 1975). Other methods, although requiring animals fitted with rumen fistulae only, are dependent on the collection of representative samples of rumen digesta (Walker & Nader, 1975) or on the assumption that all microbes are present in the liquid phase (Singh et al 1973) in order to calculate the size of the microbial pool. Alternatively, an injection of a known dose of rumen microbes, labelled with 35 S by an in vitro incubation procedure, may be made t Present address: Department of Animal Science, University of Alberta, Edmonton, Canada T6G 2E3.…”
Section: Introductionmentioning
confidence: 99%